Crafting Dynamic Characters. - Kole, Mary; Master Teaching Assistant, Writing; Brody, Jessica (linkedin.com, 2021)
To craft dynamic characters, you must remember this: connection. Learn from a bestselling author and story coach how to conceive and write memorable characters.